2016
DOI: 10.1097/dbp.0000000000000239
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Media Use on Adolescent Sleep Efficiency

Abstract: Objective In 2010, American youth ages 8-18 spent an average of 7½ hours daily using entertainment media, an increase of more than an hour compared to 2005. Increase in media use is associated with multiple negative outcomes, including decreased sleep time and increased tiredness, but little research has examined whether media use is associated with poorer sleep efficiency when the individual is actually asleep. Methods This study assessed relationships between adolescent media use and sleep efficiency. Fift… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
62
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(68 citation statements)
references
References 29 publications
5
62
0
1
Order By: Relevance
“…Two studies did not find significant associations between media use and sleep‐onset latency (Arora et al, ; Heath et al, ). Three of the studies found a significant association between bedtime social media or smartphone use and increased latency (Fobian, Avis, & Schwebel, ; Pieters et al, ; Scott & Woods, ), while one study found increased latency associated with a measure of internet addiction (Ekİncİ et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Two studies did not find significant associations between media use and sleep‐onset latency (Arora et al, ; Heath et al, ). Three of the studies found a significant association between bedtime social media or smartphone use and increased latency (Fobian, Avis, & Schwebel, ; Pieters et al, ; Scott & Woods, ), while one study found increased latency associated with a measure of internet addiction (Ekİncİ et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, incorporation of diet timing, polysomnography, hormone measurement, and cravings over a shorter time span (such as a day or week) may best capture the entire mechanism. Considering the adolescent age range, screen-time may negatively contribute to sleep efficiency, including text messages and media use after bedtime [53]. Media use may also be related to dietary quality [54] and energy intake [55], thus this additional behavior may need to be explored in the context of cravings.…”
Section: Discussionmentioning
confidence: 99%
“…This form was created by the researcher for the purpose of gathering information related to the variables that had been determined to have an impact, according to a review of the relevant literature, on the children constituting the study sample. 5,6,[11][12][13][14][15][16][17][18] On this form, the amount of time children engaged in watching TV/cinema, playing computer/console games, using internet, listening to music and playing games with mobile phones during the weekdays and at weekends was evaluated separately.…”
Section: Introductory Characteristics Of the Students And Status Of Mmentioning
confidence: 99%